2017
DOI: 10.3390/ijms18102186
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells and Tumor-Associated Macrophages in the Tumor Microenvironment in Non-Muscle Invasive Bladder Cancer Treated with Intravesical Bacille Calmette-Guérin: A Long-Term Follow-Up Study of a Japanese Cohort

Abstract: The clinical significance of regulatory T cells (Treg) and tumor-associated macrophages (TAM) in the tumor microenvironment of human bladder cancer remains unclear. The aim of this study is to explore their relevance to oncological features in non-muscle invasive bladder cancer (NMIBC). We carried out immunohistochemical analysis of forkhead box P3 (FOXP3, Treg maker), CD204 (TAM marker), and interleukin-6 (IL6) using surgical specimens obtained from 154 NMIBC patients. The Treg and TAM counts surrounding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 34 publications
4
76
1
Order By: Relevance
“…We previously reported that the accumulation of immune-suppressive cells such as regulatory T cells and tumor-associated macrophages in the baseline tumor microenvironment is associated with poor response to intravesical BCG. 31 chemotherapy, other immunotherapy drugs, and radiotherapy. 33,34 The present study is the first to investigate the potential combination of conventional chemotherapy with two different immunotherapies comprising a PD-L1 inhibitor and exogenous GM-CSF in the neoadjuvant setting of radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the accumulation of immune-suppressive cells such as regulatory T cells and tumor-associated macrophages in the baseline tumor microenvironment is associated with poor response to intravesical BCG. 31 chemotherapy, other immunotherapy drugs, and radiotherapy. 33,34 The present study is the first to investigate the potential combination of conventional chemotherapy with two different immunotherapies comprising a PD-L1 inhibitor and exogenous GM-CSF in the neoadjuvant setting of radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the TAMs are localized in the stroma-tumor margin of NMIBC, infiltrating the tumor area in high-grade tumors, another immunosuppressive cell type the Tregs localize in the stroma around the cancer lesion regardless of tumor stage and grade (9). High Treg counts were shown to be an independent predictor for recurrence following BCG treatment (7,9).…”
Section: The Gold Standard Immunomodulatory Approach To Treat Nmibc: mentioning
confidence: 99%
“…Several published reports have provided evidence that a predominance of immunosuppressive cell types are associated with BCG immunotherapy failure. In particular, the presence of M2-like tumor associated macrophages (TAMs) has consistently been associated with shorter recurrence-free survival and thus a poor response to BCG (7,(9)(10)(11). In NMIBC these TAMs are induced and maintained by Bone Morphogenetic Protein 4 (BMP4) secreted by the tumor cells (12).…”
Section: The Gold Standard Immunomodulatory Approach To Treat Nmibc: mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that TAMs are associated with poor prognosis of tumors [11][12]. Particularly, the density of TAMs is closely associated with the poor prognosis of some solid tumors, such as breast cancer, gastric cancer, lung cancer, and bladder cancer [13][14]. Thus, the recruitment of macrophages to the TME is important before the transformation to TAMs.…”
Section: Ivyspringmentioning
confidence: 99%